Preparation method of basalt fiber reinforced environmentally friendly building material
Through the basalt fiber-reinforced environmentally friendly building materials preparation method, the problems of poor mechanical properties and insufficient high temperature resistance of existing building materials are solved, and the effects of high compressive and tensile strength are achieved, while reducing environmental impact.
Patent Information
- Application Number
- CN202411096247.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The mechanical properties of existing building materials are poor and are prone to moisture and mold, and the high temperature resistance of sound insulation and fire-proof materials needs to be improved.
The preparation method of environmentally friendly building materials reinforced by basalt fibers is adopted. By stirring and mixing the components such as gelling materials, blends, basalt fibers, nano SiO2 dispersions, polycarboxylate water reducers, tackifiers, coagulant accelerators and lubricants, the slurry is formed and cured at room temperature for 28 days.
It significantly improves the compressive strength and split tensile strength of building materials, enhances the interfacial strength and overall performance of the materials, and reduces the impact on the environment through environmental protection properties.
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, in particular to a method for preparing a basalt fiber-reinforced environmentally friendly building material. Background Art
[0002] Basalt fiber concrete is a building material in which basalt fibers can improve the connectivity and microstructure of concrete aggregates, thereby affecting the mechanical properties.
[0003] Chinese patent CN115925328B: discloses a high sound insulation and fireproof building material and a preparation method thereof, belonging to the technical field of building materials. The present invention is used to solve the technical problems that the mechanical properties of the sound insulation and fireproof building materials in the prior art are poor, they are easily affected by moisture and mildew, and the high temperature resistance of the sound insulation and fireproof building materials needs to be further improved. A high sound insulation and fireproof building material is prepared by mixing 20-30 parts of kaolin, 15-20 parts of basalt fiber, 2-3 parts of foaming agent, 3.5-5 parts of modified flame retardant, 5-7.5 parts of modified polystyrene and 2-3 parts of additives in parts by weight, and adding them into an extruder.
[0004] Chinese patent CN116553876B: relates to the field of building materials, specifically an energy-saving green building material and its preparation method, which includes the following components by weight: 800-1000 parts of cement, 400-600 parts of recycled aggregate, 100-200 parts of quartz powder, 50-100 parts of basalt fiber, 10-30 parts of foam particles, 5-10 parts of additives, and 200-300 parts of water.
[0005] Chinese patent CN114605106B: discloses a composite building material and its preparation method, which comprises the following raw materials by weight: 10-20 parts of calcium silicate powder, 15-25 parts of aluminum silicate powder, 5-10 parts of magnesium oxide, 10-15 parts of low-density polyethylene resin, 8-12 parts of modified basalt-montmorillonite composite material, and 0.5-1 part of carbon black.
[0006] However, the building materials prepared by the above patents and prior art have poor compressive strength, cracks are continuous, large pieces of cement blocks fall off the surface, and the integrity of the test blocks cannot be maintained; as the load continues to increase, the internal stress of the test blocks increases, the main cracks start to expand upward from the bottom along the center, and the splitting tensile strength is poor. Summary of the invention
[0007] In view of the above problems, the present invention provides a method for preparing a basalt fiber reinforced environmentally friendly building material, and the operating steps are as follows:
[0008] S1: According to weight, weigh 100-140 parts of cementitious materials, 50-70 parts of admixtures, 10-20 parts of medium sand, and 25-35 parts of crushed stone, and stir and mix for 10-15 minutes;
[0009] S2: Continue to add 0.1-1 parts of basalt fiber, 0.1-1 parts of Γ-(2,3) epoxy (propoxy) propyl triethoxy silane, and 0.5-2 parts of nano-SiO2 dispersion, and stir and mix for 10-20 minutes;
[0010] S3: Continue to add 0.1-1 part of polycarboxylate water reducer, 0.01-0.06 part of viscosity enhancer, 0.01-0.06 part of coagulant, 0.1-0.5 part of lubricant, and stir and mix for 5-10 minutes;
[0011] S4: adding water to the mixture according to a certain water-cement ratio and mixing evenly to obtain slurry;
[0012] S5: Pour the slurry into a mold and cure at room temperature for 28 days.
[0013] Furthermore, the cementitious material is one of ordinary Portland cement, rapid hardening Portland cement, high alumina cement and sulphoaluminate cement.
[0014] Furthermore, the admixture is one of microsilica powder, fly ash, lime, bottom ash of kiln, waste glass, foamed polyethylene particles, ceramsite, and polyurethane foam.
[0015] Furthermore, the coagulant is lithium carbonate.
[0016] Furthermore, the lubricant is triglycerol dioleate.
[0017] Furthermore, the water-cement ratio is controlled at 0.42-0.50.
[0018] Furthermore, the tackifier is an organotin modified tackifier, and the preparation method thereof comprises the following steps:
[0019] K1: Plasma surface treatment of ethylene-vinyl acetate copolymer, using radio frequency or microwave power, operating under low pressure environment, to obtain mercapto-modified ethylene-vinyl acetate copolymer;
[0020] K2: Add the following chemical substances to the stirred reactor in the following proportions: 0.8-2.3 parts of 3-butyl allyl tin, 0.02-0.5 parts of 1-(4,6-diamino-1,3,5-triazine-2-yl)guanidine, 200-300 parts of toluene, 2-5 parts of tert-butyl alcohol, heat the mixture to 60-70°C and stir for 30-100 minutes, then add 50-70 parts of mercapto-modified ethylene-vinyl acetate copolymer; stir at 60-70°C for 40-80 minutes, remove toluene by distillation, cool and collect the organotin-modified tackifier after completion.
[0021] Furthermore, the plasma treatment parameters are: the power frequency is set to 13.56 MHz radio frequency, the power range is 50-300 watts, the operating pressure is 50-200 mTorr, and the treatment time is 5-30 minutes.
[0022] Furthermore, the plasma gas is thioglycolic acid vapor with a flow rate of 15-30 ml / min.
[0023] The reaction mechanism of the above technical solution:
[0024] Thiol-olefin addition reaction with 3-butylallyltin: This reaction is based on thiol-olefin click chemistry, in which the olefin moiety in 3-butylallyltin reacts efficiently with the thiol group in 1-(4,6-diamino-1,3,5-triazin-2-yl)guanidine to form a thioether linkage through a free radical intermediate.
[0025] Mercapto-epoxy ring-opening reaction with mercapto-modified ethylene-vinyl acetate copolymer: In this process, the epoxy group in 3-butyl allyl tin undergoes a ring-opening polymerization reaction with the mercapto group in the mercapto-modified ethylene-vinyl acetate copolymer; the mercapto-epoxy reaction is a typical base-catalyzed reaction to generate thioether links, and the process has the characteristics of high conversion rate and rapid reaction.
[0026] The method of the present invention has the following advantages over the prior art:
[0027] 1. The mercapto-olefin addition reaction with 3-butyl allyl tin introduces organic tin and triazine functional groups, which enhances the mechanical properties and heat resistance of the polymer. At the same time, the high selectivity and efficiency of the mercapto-olefin reaction enable the material to cure quickly under mild conditions, making it suitable for rapid manufacturing and repair.
[0028] 2. The mercapto-epoxy ring-opening reaction with mercapto-modified ethylene-vinyl acetate copolymer enhances the adhesion and chemical stability of the material, which is particularly suitable for applications requiring high-strength bonding, such as structural bonding and the preparation of composite materials; at the same time, the rapidity of the mercapto-epoxy reaction brings high efficiency to production.
[0029] Combining the new functional groups brought about by the above-mentioned chemical reactions can significantly improve the interface strength and overall performance of the material; using modified basalt fiber as a reinforcing material can not only improve the mechanical properties of building materials, but also reduce the impact of buildings on the environment through its environmentally friendly properties. DETAILED DESCRIPTION
[0030] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0031] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0032] Test method:
[0033] The mechanical strength of concrete was tested using a microcomputer-controlled automatic pressure testing machine (YAW-300B).
[0034] Example 1
[0035] A method for preparing a basalt fiber reinforced environmentally friendly building material, the operating steps of which are:
[0036] S1: Weigh 100g of cementitious material, 50g of admixture, 10g of medium sand, and 25g of crushed stone, and stir and mix for 10min;
[0037] S2: Continue to add 0.1g basalt fiber, 0.1g Γ-(2,3) epoxy (propoxy) propyl triethoxy silane, and 0.5g nano-SiO2 dispersion, and stir and mix for 10min;
[0038] S3: Continue to add 0.1g polycarboxylate water reducer, 0.01g viscosity enhancer, 0.01g coagulant, and 0.1g lubricant, and stir and mix for 5min;
[0039] S4: adding water to the mixture according to a certain water-cement ratio and mixing evenly to obtain slurry;
[0040] S5: Pour the slurry into a mold and cure at room temperature for 28 days.
[0041] The cementitious material is ordinary Portland cement.
[0042] The admixture is microsilica powder.
[0043] The coagulant is lithium carbonate.
[0044] The lubricant is triglycerol dioleate.
[0045] The water-cement ratio is controlled at 0.42.
[0046] The tackifier is an organotin modified tackifier, and the preparation method thereof comprises the following steps:
[0047] K1: Plasma surface treatment of ethylene-vinyl acetate copolymer, using radio frequency and operating in a low-pressure environment to obtain mercapto-modified ethylene-vinyl acetate copolymer;
[0048] K2: Add the following chemical substances to the stirred reactor in the following proportions: 0.8 g 3-butyl allyl tin, 0.02 g 1-(4,6-diamino-1,3,5-triazine-2-yl)guanidine, 200 g toluene, 2 g tert-butyl alcohol, heat the mixture to 60°C and stir for 30 minutes, then add 50 g mercapto-modified ethylene-vinyl acetate copolymer; stir at 60°C for 40 minutes, remove toluene by distillation, cool and collect the organotin-modified tackifier after completion.
[0049] The plasma treatment parameters are: the power frequency is set to 13.56 MHz radio frequency, the power range is 50 watts, the operating pressure is 50 mTorr, and the treatment time is 5 minutes.
[0050] The plasma gas is thioglycolic acid vapor with a flow rate of 15 ml / min.
[0051] After testing and analysis, the environmentally friendly building material prepared in this example has a 28-day compressive strength of 49.5 MPa and a 28-day splitting tensile strength of 4.69 MPa.
[0052] Example 2
[0053] A method for preparing a basalt fiber reinforced environmentally friendly building material, the operating steps of which are:
[0054] S1: Weigh 110g of cementitious material, 55g of admixture, 13g of medium sand, and 28g of crushed stone, and stir and mix for 12 minutes;
[0055] S2: Continue to add 0.5g basalt fiber, 0.5g Γ-(2,3) epoxy (propoxy) propyl triethoxy silane, 1g nano-SiO2 dispersion, and stir and mix for 15min;
[0056] S3: Continue to add 0.5g polycarboxylate water reducer, 0.02g viscosity enhancer, 0.02g coagulant, and 0.2g lubricant, and stir and mix for 6 minutes;
[0057] S4: adding water to the mixture according to a certain water-cement ratio and mixing evenly to obtain slurry;
[0058] S5: Pour the slurry into a mold and cure at room temperature for 28 days.
[0059] The cementitious material is fast-hardening silicate cement.
[0060] The admixture is fly ash.
[0061] The coagulant is lithium carbonate.
[0062] The lubricant is triglycerol dioleate.
[0063] The water-cement ratio is controlled at 0.44.
[0064] The tackifier is an organotin modified tackifier, and the preparation method thereof comprises the following steps:
[0065] K1: Plasma surface treatment of ethylene-vinyl acetate copolymer, using radio frequency and operating in a low-pressure environment to obtain mercapto-modified ethylene-vinyl acetate copolymer;
[0066] K2: Add the following chemical substances to the stirred reactor in the following proportions: 1.2 g 3-butyl allyl tin, 0.2 g 1-(4,6-diamino-1,3,5-triazine-2-yl)guanidine, 240 g toluene, 3 g tert-butyl alcohol, heat the mixture to 65°C and stir for 50 minutes, then add 55 g mercapto-modified ethylene-vinyl acetate copolymer; stir at 65°C for 50 minutes, remove toluene by distillation, cool and collect the organotin-modified tackifier after completion.
[0067] The plasma treatment parameters are: the power frequency is set to 13.56 MHz radio frequency, the power range is 100 watts, the operating pressure is 100 mTorr, and the treatment time is 10 minutes.
[0068] The plasma gas is thioglycolic acid vapor with a flow rate of 20 ml / min.
[0069] After testing and analysis, the environmentally friendly building material prepared in this example has a 28-day compressive strength of 50.7 MPa and a 28-day splitting tensile strength of 4.73 MPa.
[0070] Example 3
[0071] A method for preparing a basalt fiber reinforced environmentally friendly building material, the operating steps of which are:
[0072] S1: Weigh 130g of cementitious material, 65g of admixture, 18g of medium sand, and 33g of crushed stone, and stir and mix for 14min;
[0073] S2: Continue to add 0.8g basalt fiber, 0.8g Γ-(2,3) epoxy (propoxy) propyl triethoxy silane, 1.5g nano-SiO2 dispersion, and stir and mix for 15min;
[0074] S3: Continue to add 0.18g polycarboxylate water reducer, 0.05g viscosity enhancer, 0.05g coagulant, and 0.4g lubricant, and stir and mix for 8min;
[0075] S4: adding water to the mixture according to a certain water-cement ratio and mixing evenly to obtain slurry;
[0076] S5: Pour the slurry into a mold and cure at room temperature for 28 days.
[0077] The cementitious material is high-alumina cement.
[0078] The admixture is lime.
[0079] The coagulant is lithium carbonate.
[0080] The lubricant is triglycerol dioleate.
[0081] The water-cement ratio is controlled at 0.46.
[0082] The tackifier is an organotin modified tackifier, and the preparation method thereof comprises the following steps:
[0083] K1: Plasma surface treatment of ethylene-vinyl acetate copolymer, using radio frequency and operating in a low-pressure environment to obtain mercapto-modified ethylene-vinyl acetate copolymer;
[0084] K2: Add the following chemical substances to the stirred reactor in the following proportions: 2 g 3-butyl allyl tin, 0.4 g 1-(4,6-diamino-1,3,5-triazine-2-yl)guanidine, 280 g toluene, 4 g tert-butyl alcohol, heat the mixture to 65°C and stir for 80 minutes, then add 65 g mercapto-modified ethylene-vinyl acetate copolymer; stir at 65°C for 70 minutes, remove toluene by distillation, cool and collect the organotin-modified tackifier after completion.
[0085] The plasma treatment parameters are: the power frequency is set to 13.56 MHz radio frequency, the power range is 200 watts, the operating pressure is 150 mTorr, and the treatment time is 20 minutes.
[0086] The plasma gas is thioglycolic acid vapor with a flow rate of 25 ml / min.
[0087] After testing and analysis, the environmentally friendly building material prepared in this example has a 28-day compressive strength of 51.6 MPa and a 28-day splitting tensile strength of 4.76 MPa.
[0088] Example 4
[0089] A method for preparing a basalt fiber reinforced environmentally friendly building material, the operating steps of which are:
[0090] S1: Weigh 140g of cementitious material, 70g of admixture, 20g of medium sand, and 35g of crushed stone, and stir and mix for 15min;
[0091] S2: Continue to add 1g basalt fiber, 1g Γ-(2,3) epoxy (propoxy) propyl triethoxy silane, and 2g nano-SiO2 dispersion, and stir and mix for 20min;
[0092] S3: Continue to add 1g polycarboxylate water reducer, 0.06g viscosity enhancer, 0.06g coagulant, and 0.5g lubricant, and stir and mix for 10 minutes;
[0093] S4: adding water to the mixture according to a certain water-cement ratio and mixing evenly to obtain slurry;
[0094] S5: Pour the slurry into a mold and cure at room temperature for 28 days.
[0095] The cementitious material is sulphoaluminate cement.
[0096] The admixture is the bottom ash of the kiln.
[0097] The coagulant is lithium carbonate.
[0098] The lubricant is triglycerol dioleate.
[0099] The water-cement ratio is controlled at 0.50.
[0100] The tackifier is an organotin modified tackifier, and the preparation method thereof comprises the following steps:
[0101] K1: Plasma surface treatment of ethylene-vinyl acetate copolymer, using radio frequency and operating in a low-pressure environment to obtain mercapto-modified ethylene-vinyl acetate copolymer;
[0102] K2: Add the following chemical substances to the stirred reactor in the following proportions: 2.3 g 3-butyl allyl tin, 0.5 g 1-(4,6-diamino-1,3,5-triazine-2-yl)guanidine, 300 g toluene, 5 g tert-butyl alcohol, heat the mixture to 70°C and stir for 100 minutes, then add 70 g mercapto-modified ethylene-vinyl acetate copolymer; stir at 70°C for 80 minutes, remove toluene by distillation, cool and collect the organotin-modified tackifier.
[0103] The plasma treatment parameters are: the power frequency is set to 13.56 MHz radio frequency, the power range is 300 watts, the operating pressure is 200 mTorr, and the treatment time is 30 minutes.
[0104] The plasma gas is thioglycolic acid vapor with a flow rate of 30 ml / min.
[0105] After testing and analysis, the environmentally friendly building material prepared in this example has a 28-day compressive strength of 52.8 MPa and a 28-day splitting tensile strength of 4.78 MPa.
[0106] Comparative Example 1
[0107] No organotin modified tackifier was added, and the rest was the same as in Example 1.
[0108] After testing and analysis, the environmentally friendly building material prepared in this example has a 28-day compressive strength of 39.2 MPa and a 28-day splitting tensile strength of 3.91 MPa.
[0109] Comparative Example 2
[0110] The other steps were the same as in Example 1 except that 3-butyl allyl tin was not added.
[0111] After testing and analysis, the environmentally friendly building material prepared in this example has a 28-day compressive strength of 43.3 MPa and a 28-day splitting tensile strength of 4.25 MPa.
[0112] Comparative Example 3
[0113] The other steps were the same as in Example 1 except that 1-(4,6-diamino-1,3,5-triazine-2-yl)guanidine was not added.
[0114] After testing and analysis, the environmentally friendly building material prepared in this example has a 28-day compressive strength of 44.1 MPa and a 28-day splitting tensile strength of 4.31 MPa.
[0115] Through the data analysis of the above embodiments and comparative examples, the building material prepared by the present invention has high 28-day compressive strength and high 28-day splitting tensile strength, which can significantly improve the interface strength and overall performance of the material.
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a basalt fiber reinforced environmentally friendly building material, the operating steps of which are: S1: According to weight, weigh 100-140 parts of cementitious materials, 50-70 parts of admixtures, 10-20 parts of medium sand, and 25-35 parts of crushed stone, and stir and mix for 10-15 minutes; S2: Continue to add 0.1-1 parts of basalt fiber, 0.1-1 parts of Γ-(2,3) epoxy (propoxy) propyl triethoxy silane, and 0.5-2 parts of nano-SiO2 dispersion, and stir and mix for 10-20 minutes; S3: Continue to add 0.1-1 part of polycarboxylate water reducer, 0.01-0.06 part of viscosity enhancer, 0.01-0.06 part of coagulant, 0.1-0.5 part of lubricant, and stir and mix for 5-10 minutes; S4: adding water to the mixture according to a certain water-cement ratio and mixing evenly to obtain slurry; S5: pour the slurry into a mold and cure at room temperature for 28 days; The tackifier is an organotin modified tackifier, and the preparation method thereof comprises the following steps: K1: Plasma surface treatment of ethylene-vinyl acetate copolymer, using radio frequency or microwave power, operating under low pressure environment, to obtain mercapto-modified ethylene-vinyl acetate copolymer; K2: Add the following chemical substances to the stirred reactor in the following proportions: 0.8-2.3 parts of 3-butyl allyl tin, 0.02-0.5 parts of 1-(4,6-diamino-1,3,5-triazine-2-yl)guanidine, 200-300 parts of toluene, 2-5 parts of tert-butyl alcohol, heat the mixture to 60-70°C and stir for 30-100 minutes, then add 50-70 parts of mercapto-modified ethylene-vinyl acetate copolymer; stir at 60-70°C for 40-80 minutes, remove toluene by distillation, cool and collect the organotin-modified tackifier after completion.
2. The method for preparing a basalt fiber reinforced environmentally friendly building material according to claim 1, characterized in that: The cementitious material is one of ordinary silicate cement, rapid hardening silicate cement, high alumina cement and sulphoaluminate cement.
3. The method for preparing a basalt fiber reinforced environmentally friendly building material according to claim 1, characterized in that: The admixture is one of microsilica powder, fly ash, lime, bottom ash of kiln, waste glass, foamed polyethylene particles, ceramsite and polyurethane foam.
4. The method for preparing a basalt fiber reinforced environmentally friendly building material according to claim 1, characterized in that: The coagulant is lithium carbonate.
5. The method for preparing a basalt fiber reinforced environmentally friendly building material according to claim 1, characterized in that: The lubricant is triglycerol dioleate.
6. The method for preparing a basalt fiber reinforced environmentally friendly building material according to claim 1, characterized in that: The water-cement ratio is controlled at 0.42-0.
50.
7. The method for preparing a basalt fiber reinforced environmentally friendly building material according to claim 1, characterized in that: The plasma treatment parameters are: the power frequency is set to 13.56 MHz radio frequency, the power range is 50-300 watts, the operating pressure is 50-200 mTorr, and the treatment time is 5-30 minutes.
8. The method for preparing a basalt fiber reinforced environmentally friendly building material according to claim 1, characterized in that: The plasma gas is thioglycolic acid vapor with a flow rate of 15-30 ml / min.
Citation Information
Patent Citations
A composite building material and its preparation method
CN114605106B
A high sound insulation and fireproof building material and preparation method thereof
CN115925328B
Energy-saving green building material and preparation method thereof
CN116553876B
Basalt fiber reinforced cement based material and preparation method therefor
CN105541209A